Social Media Usage Among Students: Engagement and Performance (Swarnadwar, 2025)
Social Media (SM) has become integral part of everyone life, it is inevitable in this global era. Influence of social media on everyone’s life can be positive or negative or both that depends on the how much time students spends on social media and for what purpose or activities do they use social medias. This study has set three research objectives: first one is to study which of the channel of social media is most preferred by the students second is to figure out how much time students spend on social media and third is to assess the significance of social media usage on students’ academic and non-academic performance, with a focus on gender differences. The population of this study is students of BBA (Bachelor in Business Administration) and BBM (Bachelor of Business Management) program of different campuses of Bhaktapur district which are running under TU (Tribhuvan University), Nepal. This study has taken 205 respondents for sample from BBA and BBM programs through using Purposive sampling method. Primary data are used and they are collected from well-structured questionnaire that has included close ended and five Likert scale (1=strongly disagree, to 5=Strongly agree) questions to meet the research objectives. Mean, frequency, percentage and t-test are used to analyze the data. This study has found that Instagram is highly preferred social media and highest size of students spent their time more than 7 hours in a day. It has found that most of students have used social medias for non-academic performance. This study has found significant difference between male and female students regarding the use social medias for academic performance, but there is no significance difference between male and female students regarding the use social medias for non- academic performance.